TOOLS FOR INCREASING THE COMPETITIVENESS OF ENTERPRISES USING MARKETING COMMUNICATIONS - YAKUBENKO, Yuliia; POLYOVA, Nataliya (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article substantiates the importance of using a wide range of tools in increasing the competitiveness of the enterprise, and the main attention is paid to the implementation of marketing communication tools. A number of features of marketing communications related to information-analytical, technical-technological, organizational-management, economic and other areas of resource provision are emphasized. Priority is given to the development and implementation of marketing strategies, which will take into account market trends, the level of competition, the formation of competitive advantages and other aspects in the formation of the overall management system for the processes of increasing the competitiveness of the enterprise. The toolkit for increasing the competitiveness of enterprises by means of marketing communications is summarized. Increasing the competitiveness of the enterprise by means of marketing communications is complex, and its vectors should be considered as (1) modernization and implementation of price policy, which would create a long-term stable state in conditions of high intensity of competition, (2) formation of a product range that meets the needs of potential buyers and systematic acquisition profit, (3) analysis and monitoring of markets for potential goods (services) that correspond to the choice of strategic business areas, (4) prediction of crisis trends both within the industry and within the enterprise from the point of view of marketing new areas of business activity, (5) distribution of existing resources between different areas of activity, which would ensure the maximum effectiveness of marketing activities, (6) marketing studies of the conditions for the formation of competitive advantages and the implementation of promotional measures to increase them.